Design and application research on data service platform for big data - Yun-feng LIU; Li LI; Su-mei WANG; Qian-yi WANG; Xu YANG; Rong-bin OUYANG; Xin-zheng LONG (Tongxin xuebao)
Big data management gives challenges to data manage and service platform based on traditional relational database management system,and research on big data management and service platform supporting both structured and unstructured data has become a very urgent and important task.4 key technologies for big data management service platform was summarized,and the configurable generalization table model was adopt.The data service center system prototype BIG-DMS based on Hadoop platform and the application scheme of data integration services platform based on BIG-DMS were also designed to support both structured and unstructured data storage,management and access services.